(untitled) (AYUSHDHARA, 2025)
The concept of Sira (channels or vessels) is a crucial aspect of Ayurvedic physiology, playing a vital role in the circulation of essential bodily substances such as Rasa (bodily fluids), Rakta (blood), Ojas (vital essence) and Prana (life force). Rooted in the foundational texts of Ayurveda, especially the Sushruta Samhita and Charaka Samhita, Sira is described as a network of channels responsible for transporting nutrients, energy, and waste products throughout the body. The proper functioning of Sira ensures the nourishment of Dhatus (tissues) and Marma points (vital energy centers), maintains immunity, and facilitates detoxification. The article explores the theoretical significance of Sira as a vital structure in Ayurvedic medicine, examining its relationship with other circulatory components like Dhamani (arteries) and Srotas (pathways). It also highlights the impact of imbalances in Sira circulation, which can lead to various health conditions associated with the disturbance of Vata, Pitta, and Kapha doshas. By addressing the health of the Sira system, Ayurveda offers holistic approaches to restore balance and promote vitality. The references drawn from specific chapters in the Sushruta Samhita and Charaka Samhita underscore the importance of Sira in maintaining the overall health of the body and mind. This abstract summarizes the article’s key points on Sira’s role in Ayurvedic physiology, drawing from the classical texts and linking it to broader health concepts.